Pemilihan Media Pembelajaran Yang Tepat Untuk Meningkatkan Hasil Pencapaian Belajar Peserta Didik - Azzahra Kamila Cahyani Masdar; Lailatun Nadira; Yova Murnika; Wismanto Wismanto (Lembaga Pengembangan Kinerja Dosen, 2024)
By using learning media, educators can increase students' interest in learning new things through teaching materials that are easy to understand. Learning media that is interesting for students can be a stimulus for students in the learning process. As an educator, you must be able to choose and use learning media quickly and appropriately to help achieve the learning objectives that have been set. The purpose of the study was to explore the selection of the right learning media model to improve students' learning achievement results. This research method is a qualitative research based on literature (library research). This research is taken based on the sources that the author gets, both in the form of; articles, journals, books, magazines and so on related to the research theme. This research examines the selection of appropriate learning media to improve student learning outcomes. The results of this study indicate that one of the factors supporting the success of the learning activity process is the use of learning media. Learning media is very important in supporting classroom learning activities so that it is expected to realize a good teaching and learning process and have a positive impact on learning outcomes so that students can achieve educational goals and student learning outcomes become better.